Evaluasi Kognitif dan Psikomotorik Berbasis Moderasi Beragama: Konsep dan Penerapannya Dalam Pembelajaran PAI dan Budi Pekerti - Hasan, Munawir (El-Suffah: Jurnal Studi Islam, 2024)
The objective of this study is to describe the evaluation conducted by teachers in the teaching of Islamic Religious Education (PAI) and Character Education integrated with religious moderation in the cognitive and psychomotor aspects at SD Negeri 03 Pontianak Kota District. This study uses both quantitative and qualitative approaches. The results show that the cognitive assessment in the teaching of Islamic Religious Education (PAI) and Character Education at SD Negeri 03 Pontianak Kota is carried out through written tests. The competencies evaluated include students' understanding of religious teachings and the application of moral values. The psychomotor assessment is conducted through an attitude assessment rubric, which includes evaluating students' skills and attitudes that can be observed physically or practically. The connection to religious moderation emphasizes attitudes of tolerance, respect for diversity, and the implementation of religious teachings in real actions.  Keywords: Evaluation, Learning, Cognitive, Psychomotor, Religious Moderation  Abstrak: Tujuan dalam penelitian ini untuk mendeskripsikan evaluasi yang dilakukan oleh Guru dalam pembelajaran Pendidikan Agama Islam (PAI) dan Budi Pekerti yang terintegrasi dengan moderasi beragama pada aspek kognitif dan psikomotorik di SD Negeri 03 Kecamatan Pontianak Kota. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa penilaian kognitif  pembelajaran Pendidikan Agama Islam (PAI) dan Budi Pekerti di SD Negeri 03 Pontianak Kota melalui tes tertulis. Kompetensi yang dievalausi  adalah pemahaman siswa terhadap ajaran agama dan penerapan nilai-nilai budi pekerti. Penilaian psikomotorik melalui rubrik penilaian sikap  yang mencakup penilaian terhadap keterampilan dan sikap siswa yang dapat diamati secara fisik atau praktis. Pengaitannya dengan moderasi beragama menekankan pada sikap toleransi, penghargaan terhadap keberagaman, dan implementasi ajaran agama dalam tindakan nyata.